2012
DOI: 10.1021/ef300938r
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Polyethylene into Transportation Fuels by the Combination of Thermal Cracking and Catalytic Hydroreforming over Ni-Supported Hierarchical Beta Zeolite

Abstract: The oil obtained from the thermal cracking of low-density polyethylene (LDPE) is formed mainly by linear hydrocarbons with a high quantity of olefins, which hinders the possible application of this product in the formulation of transportation fuels. However, hydroreforming of this oil using bifunctional catalysts with high accessibility to the active sites would allow for the properties of the gasoline and diesel fractions to be significantly upgraded. This is the case of the catalyst employed here because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…The addition of metal improved the formation of benzene, toluene, and napthalenes. The aromatic compounds produced during catalytic run were in the range of gasoline (C 5 eC 12 ) [46]. Therefore, these aromatics could improve heating value in bio-oil.…”
Section: Aromatic Distribution and Selectivitymentioning
confidence: 99%
“…The addition of metal improved the formation of benzene, toluene, and napthalenes. The aromatic compounds produced during catalytic run were in the range of gasoline (C 5 eC 12 ) [46]. Therefore, these aromatics could improve heating value in bio-oil.…”
Section: Aromatic Distribution and Selectivitymentioning
confidence: 99%
“…39,52 To get more information on the acidity changes, pyridine adsorption was conducted to quantify the Brönsted and Lewis acid sties on the zeolites. 39,40,52 3.2. In contrast, the Lewis acid sites on the zeolites increased signicantly aer P and especially Ni impregnation (see Table 1).…”
Section: Catalyst Characterizationsmentioning
confidence: 99%
“…and it has been found that Ni/hierarchical Beta zeolite (Ni/h-Beta) provides a high selectivity to the desired products, gasoline and automotive diesel (55% and 27%, respectively) [14]. These results were ascribed to the bimodal microporous/mesoporous pore structure of the hierarchical Beta zeolite, which allows a better accessibility of the reagents toward the acid sites as well as an improved dispersion of the nickel active phase.…”
Section: Introductionmentioning
confidence: 99%